Effect of Season and Dietary Protein Level on Some Haematological Parameters and Blood Biochemical Compositions of Three Broiler Strains - Mohamed, E.A.A.; Ali, O.H.A.; Malik , Huwaida, E.E.; Yousif, I.A. (International Journal of Poultry Science, 2012)
The objectives of the present study were to investigate the effect of season (summer versus winter) and dietary protein level (high versus low) using three broiler strains (Ross, Cobb and Hubbard) on some physiological parameters; haematological parameters, haematological indices, serum metabolites and serum inorganic elements. Three hundred and sixty, one-day-old unsexed broiler chicks, were used during the summer and winter seasons, 120 from each strain. The number of chicks of each strain was divided into two groups, with six replicates (10 chicks per each). Group A of each strain was fed on a starter diet containing 23% crude protein for the first four weeks of age, replaced by a finisher diet containing 21% crude protein. Group B was fed on a starter diet containing 21% crude protein replaced by a finisher diet containing 19% crude protein. In both Cobb and Hubbard strains, the Packed Cell Volume (PCV) decreased significantly (P<0.05) during the summer season, whereas, it was significantly (P<0.05) increased in Ross strain during the same season. The haemoglobin concentration (Hb) decreased significantly (P<0.05) in Cobb strain during the summer. It was not significantly affected by the season in both Ross and Hubbard strains. The total red blood cells count (TRBC count) did not significantly affected by the season in the three experimental strains. The Mean Cell Volume (MCV) increased significantly (P<0.05) during the summer in Ross strain but it was not significantly affected by the season in both Cobb and Hubbard strains. The Mean Cell Haemoglobin (MCH) decreased significantly (P<0.05) during the summer in both Ross and Cobb strains but it was not significantly affected by the season in Hubbard strain. The Mean Cell Haemoglobin Concentration (MCHC) decreased significantly (P<0.05) during the summer in the three experimental groups. Serum glucose concentration decreased significantly (P<0.05) during the summer in both Ross and Hubbard strains but was not affected by the season in Cobb strain. The serum albumin concentration decreased significantly (P<0.05) during the summer in Ross strain but was not significantly affected by the season in both Cobb and Hubbard strains. The results reflected that, serum sodium (Na), potassium (K) and phosphorus (P) concentrations were decreased significantly during the summer in all strains. The serum calcium (Ca) concentration decreased significantly during the summer in Cobb strain. Whereas, it was not significantly affected by the season in both Ross and Hubbard strains. Although there was broiler strain X protein level interaction effect on all of following physiological parameters; PCV, MCV, MCHC, serum glucose, serum albumin, serum Na, K, Ca and serum P, the level of dietary protein appeared to be has no significant effect on any of physiological parameters under investigation.